Operation of a steel-concrete composite beam considering slab cracking - Łagoda, Marek; Śledziewski, Krzysztof (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The theme of the paper is the effect of scratching of reinforced concrete slab on the work of a steel-concrete composite beam. The paper evaluates the state of knowledge in the field of composite structures, in particular, statically indeterminate structures with concrete in tension zones. Additionally, in a nutshell, it describes the current practice of design. Moreover, experimental studies were described on continuous beams that were made by the authors. A proposal for further work on this topic was also presented.